Effect of rotation on coherent structures in wall-bounded turbulence - W. Rojanaratanangkule (2018)
Proper orthogonal decomposition (POD) is applied to a rotating channel turbulence database generated by direct numerical simulation (DNS) to investigate the effect of spanwise rotation on the coherent structures in wall-bounded flows. The POD analysis reveals the appearance of elongated counter-rotating vortical structures at both low and moderate rotation numbers. Increasing the rotation rate results in a higher number of these elongated vortices, while reduces their size.